Potential targets of heparin during progression and metastasis of malignant neoplasms - V. V. Malashchenko; I. A. Khlusov; K. A. Yurova; O. G. Khaziakhmatova; N. M. Todosenko; L. S. Litvinova (Медицинская иммунология)
In the modern world, oncological diseases occupy the leading positions in the structure of mortality. An integrated approach to oncotherapy is not only aimed at immediate affection of malignant tumors, but also directed at reducing the risk of tumor recurrence and metastasis, as well as alleviating side effects of chemotherapy and radiotherapy of the disease. In oncologic disorders, blood viscosity increases, thus being associated with hypercoagulation syndrome. To prevent its consequences, the direct and indirect anticoagulants, especially heparin and its derivatives, are actively used. Biological functions and structural features of heparin make it a potential universal platform of a drug development for broad application, including oncology. With the advent of heparin fractionation technology and preparation of low-molecular weight forms and their derivatives, it has become possible to focus not only on anticoagulant activity but also to obtain fractions with targeted pharmacological activity. Usage of the anticoagulants has shown their antitumor activity in some cases, thus providing a basis for a more detailed study of pharmacotherapeutic effects of this group of drugs. Currently, some data suggest various pathways of interaction between heparin and tumor cells. There are multiple common features in development of a primary tumor and formation of secondary distant metastases, which may be attributed to similar molecular cellular mechanisms. The molecules mediating intercellular interactions, both between the tumor cells and between malignant cells and tumor-associated immune cells (e.g., lymphocytes and macrophages) may serve as targets for heparin thus helping the tumor to evade immune surveillance. The cytokines that stimulate tumor angiogenesis represent another important therapeutic target. Heparin derivatives are able to suppress tumor activity and prevent metastatic processes at various stages by inhibiting heparanase, P-/L-selectin, and angiogenesis activity, modulating the CXCL12-CXCR4 chemokine axis, and regulating OAM activity.This brief review addresses the current understanding and application of the potentially antimetastatic properties of heparin and its derivatives in malignant bone tumors since the heparin-based drugs are used as anticoagulants in arthroplasty of large joints and bone defects in patients with osteosarcoma.